Docência universitária: o professor de Educação Física e sua prática pedagógica - Pasenike, Sílvia Costa de Oliveira (2010)
This research focuses on Physical Education academic teaching and the relationship its professors establish between pedagogical background and their university teaching practices. Its aims include understanding such a relationship and, more specifically, identify the professor profile, what makes his/her pedagogical practice easy and what limits it, knowledge involved in the making of their teaching identity, besides verifying how a professor builds his/her pedagogical practice. This inquiry follows the quantiqualitative research approach, its data coming from questionnaires containing open and closed questions answered by Physical Education professors graduated in Physical Education teaching at two private higher education institutions. Results reveal individuals aware that pedagogical training is important to teaching although some of them do not see it as the most important requisite. They also reveal that reflexive teaching practice, professor-researcher practice, theoretical knowledge, and technical and academic training are the most important requisites to the professor s background. One hopes this study stimulates new inquiries into these matters and increases academic knowledge on professors teaching and pedagogical practice, above all Physical Education ones.